Histopathologic Predictors of Survival and Recurrence in Resected Ampullary Adenocarcinoma: International Multicenter Cohort Study. Issue 6 (December 2020) - Moekotte, Alma L.; Lof, Sanne; Van Roessel, Stijn; Fontana, Martina; Dreyer, Stephan; Shablak, Alaaeldin; Casciani, Fabio; Mavroeidis, Vasileios K.; Robinson, Stuart; Khalil, Khalid; Gradinariu, George; Mowbray, Nicholas; et al.
Abstract : Objective: The aim of the study was to define histopathologic characteristics that independently predict overall survival (OS) and disease-free survival (DFS), in patients who underwent resection of an ampullary adenocarcinoma with curative intent. Summary Background Data: A broad range of survival rates have been described for adenocarcinoma of the ampulla of Vater, presumably due to morphological heterogeneity which is a result of the different epitheliums ampullary adenocarcinoma can arise from (intestinal or pancreaticobiliary). Large series with homogenous patient selection are scarce. Methods: A retrospective multicenter cohort analysis of patients who underwent pancreatoduodenectomy for ampullary adenocarcinoma in 9 European tertiary referral centers between February 2006 and December 2017 was performed. Collected data included demographics, histopathologic details, survival, and recurrence. OS and DFS analyses were performed using Kaplan–Meier curves and Cox proportional hazard models. Results: Overall, 887 patients were included, with a mean age of 66 ± 10 years. The median OS was 64 months with 1-, 3-, 5-, and 10-year OS rates of 89%, 63%, 52%, and 37%, respectively. Histopathologic subtype, differentiation grade, lymphovascular invasion, perineural invasion, T-stage, N-stage, resection margin, and adjuvant chemotherapy were correlated with OS and DFS. N-stage (HR = 3.30 [2.09–5.21]), perineural invasion (HR = 1.50 [1.01–2.23]), and adjuvant chemotherapy (HR = 0.69 [0.48–0.97]) were independent predictors of OS in multivariable analysis, whereas DFS was only adversely predicted by N-stage (HR = 2.65 [1.65–4.27]). Conclusions: Independent predictors of OS in resected ampullary cancer were N-stage, perineural invasion, and adjuvant chemotherapy. N-stage was the only predictor of DFS. These findings improve predicting survival and recurrence after resection of ampullary adenocarcinoma. Abstract : Supplemental Digital Content is available in the text